6 - Digital Learning Response in the Midst of the Covid-19 Pandemic: The Case of Mauritius - Verena Tandrayen-Ragoobur,; Boopen Seetanah,; Sheereen Fauzel,; Viraiyan Teeroovengadum, (Africa Development, 2023)
This article investigates learners’ perception of their ability to adapt to online learning and the challenges they encountered as well as the opportunities they found in this new e-learning environment, in the midst of the Covid-19 pandemic. A comprehensive survey was undertaken using an online questionnaire circulated among male and female students across various faculties at five universities and business schools in Mauritius. The results indicate that Covid-19 was a major disruption in higher education studies. Despite the online learning approach, students enrolled in STEM degrees were more impacted compared to those in non-STEM degrees. Around one-third of the students asserted that online learning was a major challenge, more so for those in the lowest-income group who lacked the necessary digital tools to adapt to this new learning environment. A non-conducive home environment further had a negative bearing on students’ concentration and ability to cope with their studies. We noted that postgraduate students adapt to digital learning better compared to undergraduates. There is thus a need to rethink, revamp and redesign the education system to be prepared for future shocks and build resilience through the application of best practices in the digitalisation of the education system.